2014
DOI: 10.1158/1055-9965.epi-14-0398
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNAs 145-3p and 145-5p Is a Long-term Predictor of Postmenopausal Breast Cancer Risk: The ORDET Prospective Study

Abstract: Background: miRNAs have been implicated in the regulation of key metabolic, inflammatory, and malignant pathways; hence, they might be considered both predictors and players of cancer development.Methods: Using a case-control study design nested in the ORDET prospective cohort study, we addressed the possibility that specific mRNAs can serve as early predictors of breast cancer incidence in postmenopausal women. We compared leukocyte miRNA profiles of 133 incident postmenopausal breast cancer cases and profile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The recent discovery of the circRNA–microRNA code, in which the two types of RNA molecules interact with one another to determine the regulation of gene expression, is a promising field of study for early detection and prognosis of cancer. Our previous studies described miRNAs that can serve as long‐term predictors of postmenopausal breast cancer risk, that is, miR‐145‐3p, miR‐145‐5p, and miR‐513a‐5p (Muti et al ., , ). To the best of our knowledge, there are no studies describing the role of circRNAs as long‐term predictors, but this role is likely to be uncovered.…”
Section: Known Mechanisms Of Action Of Circrnasmentioning
confidence: 99%
“…The recent discovery of the circRNA–microRNA code, in which the two types of RNA molecules interact with one another to determine the regulation of gene expression, is a promising field of study for early detection and prognosis of cancer. Our previous studies described miRNAs that can serve as long‐term predictors of postmenopausal breast cancer risk, that is, miR‐145‐3p, miR‐145‐5p, and miR‐513a‐5p (Muti et al ., , ). To the best of our knowledge, there are no studies describing the role of circRNAs as long‐term predictors, but this role is likely to be uncovered.…”
Section: Known Mechanisms Of Action Of Circrnasmentioning
confidence: 99%
“…Literature selection A total of 1,262 studies were identified from online databases MEDLINE, Embase, PubMed, Google Scholar, and China Biology Medicine disc. Another five studies (17,(38)(39)(40)(41) were acquired through manually screening the reference lists of relevant reviews and meta-analyses. After removing 54 duplicated publications, the remaining 1,213 studies were evaluated by carefully reading the titles and abstracts, after which 1,059 studies were excluded because of the following reasons: not tumor studies, unpublished, withdrawn articles, letters, abstracts, reviews, or meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In different studies, OS was also expressed as disease-specific survival (DSS; ref. 17) and cancer-specific survival (CSS; ref. 15), while PFS was also described as recurrence-free interval (RFI; ref.…”
Section: Outcomes and Definitionmentioning
confidence: 99%
“…The regulation of the mature 5p and 3p chains from several miRNAs has been investigated in other cancers, including colorectal, gastric, breast, lung, kidney, and bladder 36,72,[74][75][76][77] , suggesting the need to focus further studies on the two mature chains from the 272 miRNAs reported in this study. Figure 6 shows the complexity of the interactions between miRNAs and tumour suppressor genes, proto-oncogenes and oncogenes.…”
Section: Mirnas Located In Hpv Integration Sitesmentioning
confidence: 95%